DILEMA AGAMA DAN PANCASILA DI RUANG PUBLIK INDONESIA - Agus Mauluddin (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2018)
This paper aims to challenge his studies (Bonotti and Seglow, 2017; Eiedat,2017; Fenton, 2016; Kaul, 2017; Kraidy and Krikorian, 2017; Nachi, 2016), which see religion and public sphere, but minus the context of Pancasila ideology. And perfecting his study Asrori (2016) who saw religion-in this case religious education in the context of the Pancasila ideology, but minus the study of public sphere in his study. Thus, this paper seeks to synthesize the position of religion in public sphere of Indonesia which has the ideology of Pancasila, and what is the policy alternative of the religious dilemma that is